Essentials and Economic Fundamentas of a State’s Fiscal Space (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Modern trends in a state’s economic system functioning feature the multiplicity of its components, along with the dynamic structure of development and certain imbalances, caused by permanent crisis phenomena, increased economic, political, cultural, environmental risks, including a significant social tension.Studying the principles of a state’s fiscal space, one should consider its functioning and improvement prospects in the context of asymmetric development trends; spread of various geopolitical, cultural and social interactions affecting the course of economic transformations; thus completing the holistic process of a state’s fiscal space formation, among which the globalization processes obviously play a dominant role.All these factors produces a significant impact on the formation and improvement of a state’s fiscal space, since the development of any public sphere requires the use of a considerable amount of funding. In this regard, the content and causes of the fiscal space asymmetry, as well as the basis of their influence factors should be discussed.The article deals with theoretical approaches to the definition of the content of asymmetries, and provides explanation for their economic nature. Main causes for the modern economy fundamental imbalance are reviewed; peculiarities of its emergence, forms of manifestation are singled out. The author suggests a personal approach to the definition of «asymmetry of the fiscal space» notion, the reasons of their evolution, which threaten a state’s stable »socio-economic development, and influence the public welfare improvement processes.
Keywords: state’s fiscal space, fiscal policy, the fiscal space asymmetry, tax system, state regulation.